Delineation and prioritization of groundwater recharge zones in the state of Karnataka using GIS technique - KALEDHONKAR, M.J.; SETHI, RANU RANI; SRIVASTVA, R.C.; KUMAR, ASHWANI; BEHERA, SUBHA RANJAN (Journal of Soil and Water Conservation, 2022)
Delineation and prioritization of suitable areas for groundwater recharge in state of Karnataka was planned under this study. Soil properties namely, soil drainage and land capability and one aquifer property namely geology were identified as spatial themes influencing groundwater recharge with weightage as 25, 25 and 50%, respectively. Variability within theme was considered by assigning appropriate score to subtheme. “Depth to water table” was used to decide priority of recharge project. During spatial analysis for prioritization, soil drainage and land capability and geology were given 50% weightage while remaining 50% weightage was given to depth to water table. Prioritized areas were divided into different rainfall zones. The area with priority first (PR 1) and priority second (PR 2) were 15.5 and 40.23% of total area of the state, respectively. On basis of rainfall amounts and appropriate runoff coefficients, annual excess runoff amounts for groundwater recharge in respective rainfall zones were worked out and accordingly numbers of recharge structures were determined. Also, numbers of fillings for percolation pond and check dam were also considered as 3 and 5, respectively. Further, percolation ponds and check dams in priority area 1 (PR 1) of 30075 km2 were estimated as 14244 and 45928, respectively. The respective structures for priority area 2 (PR 2) of 77781 km2 were estimated as 44899 and 142936, respectively. In view of better utilization of financial resources, both percolation ponds and check dams could be adopted for priority 1 areas while only percolation ponds could be adopted for priority 2 areas.